Analysis of Shrinkages in ABS Injection Molding Parts for Automobile Applications. (2018) - Sreedharan, J.; Jeevanantham, A.K.
Abstract: Shrinkage in a molded plastic part is important in defining finishing measurements of the part. In this paper it has been tried to find effect of the injection pressure, Gate sizes and cooling system that plays on the shrinkage rate of a ABS component in automotive components during injection molding process. Finite numerical solution was used to find the solution for the physical model. Molding is widely used for producing parts in large volumes it can be used for producing complex parts and can be produced with minimum effect. Still, the setting of the process parameters has to be optimized otherwise there will be defects caused due to the process parameters, such as shrinkage. In this paper, it is tried to optimize the molding process in order to reduce the molding defects like shrinkage by using Taguchi's experimental design and the analysis of variance (ANOVA) methods